Implementation Of Sharia Accountability Enterprise Theory In Corporate Social Responsibility Of Bank Ntb Syariah And Bank Islam Brunei Darussalam - Novitasari, Sitira; Wasilah, Siti Nur (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2025)
The development of globalization encourages companies, especially Islamic banks, to involve themselves in Corporate Social Responsibility (CSR) based on the principles of Sharia Enterprise Theory (SET). The research focused on Bank NTB Syariah and Bank Islam Brunei Darussalam, analyzing their level of social responsibility disclosure. The descriptive qualitative research method was used by observing the 2022 Annual Reports of both banks. The results of this study, namely Bank NTB Syariah and Bank Islam Brunei Darussalam show commitment to vertical accountability (Allah SWT), internal horizontal (employees, customers), and external horizontal (community, environment). Both implement SET in CSR with policies that comply with sharia principles, investment in education, and involvement in environmental conservation.